Concepts in cardio-oncology: definitions, mechanisms, diagnosis and treatment strategies of cancer therapy-induced cardiotoxicity. (March 2016) - Wickramasinghe, Chanaka D; Nguyen, Kim-Lien; Watson, Karol E; Vorobiof, Gabriel; Yang, Eric H
There has been considerable improvement in cancer survival rates, primarily through improved preventive strategies and novel anticancer drugs. Cancer is now becoming a chronic illness and as such both short and long-term cardiotoxic effects of cancer therapy are becoming more apparent. This has led to the emergence of a new multidisciplinary specialty known as cardio-oncology, with the purpose of identifying patients who are at a higher risk for developing cardiotoxicity so that appropriate surveillance, treatment and follow-up strategies may be instituted early. The mechanisms of cardiotoxicity caused by commonly used anticancer agents are reviewed, along with the latest advances in diagnostic and preventative strategies, with the overall objective of allowing cancer patients to continue both lifesaving and palliative treatments for their malignancy.